Development of Hair and Scalp Shampoo Product from Cherry Beer - Phensaijai, Mongkol (Journal of Science and Technology Songkhla Rajabhat University, 2021)
The objective of this research was to study how to make a hair shampoo from cherry beer and the chemical, physical, and microbiological were analyzed. The study was found that cherry beer and both formulas hair shampoo from cherry beer showed antioxidant activity that evaluated by FRAP method. The result showed that the formula 1, formula 2 and cherry beer had antioxidant activity 4,225.41, 3545.08, 1397.54 micrograms of FeSO4 per milliliter, respectively. The result from evaluated Phenolic compounds by Folin-Ciocalteu method showed that formula 1, formula 2 and cherry beer were 2550.49, 1736.76 and 1192.65 micrograms of gallic acid per millimeter, respectively. In addition, the two formulas hair shampoo and cherry beer were tested by plate count method with 3 pathogenic microorganisms, Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans respectively. The result showed that there was no growth of pathogens.